In vitro hemocompatibility testing of medical devices - Nalezinková, Martina (Thrombosis research, 2020)
Hemocompatibility testing is essential for the safe use of medical devices that come into contact with blood. There are various evaluation methodologies. In vivo, ex vivo and in vitro systems can be used and different categories can be evaluated in different ways. This review deals with in vitro hemocompatibility testing mainly on the basis of ISO standard 10993-4 recommendations and possibly new research results. This is a summary of all tested categories, i.e. coagulation, hemolysis, hematology and activation of leukocytes and platelets and the complement system. The main principle of evaluation and the possibilities of testing using various methodologies are always described. In the next part, variants of the method of blood incubation with the tested medical device from the static system to the circulation are described. Circulation can be provided, for example, by means of the Chandler Loop or parallel-plate chambers.
Keywords: hemokoagulace; testování materiálů; In Vitro Techniques; trombocyty; Blood Platelets; Materials Testing; techniky in vitro; Humans; lidé; hemolýza; Blood Coagulation; Hemolysis